Figur perempuan mandiri dalam Al-Qur`an: Kemandirian ekonomi dan tanggung jawab spiritual - hidayah, hikmatul (Maliki Interdisciplinary Journal, 2026)
Discussions about women's independence are often understood as limited to personal freedom separated from the framework of religious values. This perspective often gives rise to the assumption that women's independence is inconsistent with Islamic teachings. This article aims to examine the concept of women's independence in the Quran, emphasizing the roles they play and the spiritual resilience displayed by women. Through a thematic approach to Quranic verses, this study demonstrates that women are positioned as subjects with moral and spiritual autonomy, capable of making life choices, and playing an active role in the social sphere. Independence, from a Quranic perspective, is not interpreted as an individualistic attitude that negates social relations, but rather as self-awareness based on faith and responsibility to Allah SWT.